Penerapan Algoritma Boyer Moore Pada Aplikasi Biografi Musisi Legendaris Dunia - Batubara, Venty Azriani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Legendary musicians are ancient musicians who lived among the people and were passed down orally. The structure of these legendary musicians is usually simple so that the songs are easily accepted by the public, especially among fans of previous musicians. Legend as a type of oral folklore not only contains stories from a collective but also contains historical elements in it. Legends can reveal some of the cultural reflections of a society. For everyone it is important to know part of the story of the musician's legend. The solution that can be done is to create a search system in the Legendary Musician application which can make it easier to search. Legendary Musician App. In the legendary musician search application, in the Legendary Musician application what will be searched is not searched naïvely (searching letter by letter). However, there is a feature in the application that helps search for words, namely by using the Boyer Moore string matching algorithm. Boyer Moore search algorithm, where the Boyer Moore algorithm works is by searching from the right and then to the left. By implementing the Boyer Moore Algorithm in the search system for the Legendary Musician application, it is hoped that the search process for legendary musician applications can be carried out more easily and quickly.